Pengaruh Profitabilitas, Cash Holding, Bonus Plan, Reputasi Auditor, dan Struktur Kepemilikan terhadap Perataan Laba pada Perusahaan yang Bergerak di Bidang Properti dan Real Estate Tahun 2019-2022 - Ellyn, Ellyn; Silvia, Rina; Rahmi, Namira Ufrida; Lubis, Irna Triannur (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this study is to determine how ownership structure, cash holdings, compensation plans, profitability, and auditor reputation affect profits smoothing in real estate and property companies between 2019 and 2022. In order to provide consistent earnings from 2019 to 2022, this study used property and real estate companies listed on the Indonesia Stock Exchange. In this study, a population of 81 companies and a sample of 15 enterprises were included. To gather the sample, targeted selection was employed. The hypothesis is tested using logistic regression analytic techniques, based on the study findings that ownership structure affects the profit smoothing of real estate enterprises. However, cash holding, bonus plans, and other factors have no bearing on the earnings smoothing of real estate and property enterprises.